PENAMBAHAN DAUN GEDI (Abelmoschus Manihot (L) Medik) SEBAGAI â€œADDITIVEâ€ DALAM AIR MINUM DAN PENGARUHNYA TERHADAP PERFORMANS AYAM KAMPUNG SUPER - Kogoya, Desben; Mandey, J S; Rumokoy, L J; Regar, M N (Universitas Sam Ratulangi, 2019)
UTILIZATION OF â€œGEDI LEAF (Abelmoschus Manihot (L) Medik) ASâ€œADDITIVEâ€ IN DRINKING WATER RELATED TO THE PERFORMANCE OF INDONESIAN SUPER NATIVE CHICKEN. Research was done to evaluate the performance of Indonesian super native chicken treated with â€œGediâ€ leaf (Abelmoschus Manihot (L) Medik) asâ€œAdditiveâ€ in drinking water. Study was conducted using hundred individuals of the Indonesian super native day old chicken. The juice of â€œGediâ€ leaf (Abelmoschus Manihot (L) Medik) was given as in forms of the four treatments as follows, drinking water without â€œGediâ€ leaf as control (P0), drinking water with 10 ml juice of â€œGediâ€ leaf per liter of drinking water (P1), drinking water with 20 ml juice of â€œGediâ€ leaf per liter of drinking water (P2), and drinking water with 30 ml juice of â€œGediâ€ leaf per liter of drinking water (P3). Treatments were applied to the birds at 6 weeks old by completely randomized design five replications at each treatment. Data were taken during 5 weeks. Feeds were using 73 percents of commercial feed added by 10 percents of corn and 17 percents of rice bran with nutritional composition of crude protein 19.49 percents, crude fiber 4.66 percents, fat 3.63 percents, Calcium 1.02 percents, Phosphorus 0.66 percents and metabolic energy of 2920 kcal/kg, all given ad libitum. Variables measurement were focused on feed consumption, drinking water consumption, average daily gain, and feed conversion. Results showed that drinking water with 30 ml juice of â€œGediâ€ leaf per liter of drinking water (P3) was not significantly different with other treatments for feed and drinking water consumption, except for average daily gain and feed conversion. The treatments of P1 and P2 were not significantly different for average daily gain, but these treatments were higher in average daily gain compared with control (P0). The highest value of feed conversion was obtained at treatment P3 and the lowest value was found at treatment P1. These values indicated that the best feed conversion was treatment P1. Therefore, it can be concluded that juice of â€œGediâ€ leaf can be used as the alternative additive feed in drinking water up to 20 ml juice of â€œGediâ€ leaf per liter of drinking water in term of high average daily gain and feed conversion of Indonesian super native chicken.Â Key words: Drinking water, â€œGediâ€ leaf, Indonesian super native chicken.